Synthetic polyploidization induces enhanced phytochemical profile and biological activities in Thymus vulgaris L. essential oil - Gupta, Neha; Bhattacharya, Soham; Dutta, Adrish; Tauchen, Jan; Landa, Přemysl; Urbanová, Klára; Houdková, Markéta; Fernández-Cusimamani, Eloy; Leuner, Olga (Scientific reports, 2024)
Essential oil from Thymus vulgaris L. has valuable therapeutic potential that is highly desired in pharmaceutical, food, and cosmetic industries. Considering these advantages and the rising market demand, induced polyploids were obtained using oryzalin to enhance essential oil yield. However, their therapeutic values were unexplored. So, this study aims to assess the phytochemical content, and antimicrobial, antioxidant, and anti-inflammatory activities of tetraploid and diploid thyme essential oils. Induced tetraploids had 41.11% higher essential oil yield with enhanced thymol and γ-terpinene content than diploid. Tetraploids exhibited higher antibacterial activity against all tested microorganisms. Similarly, in DPPH radical scavenging assay tetraploid essential oil was more potent with half-maximal inhibitory doses (IC50) of 180.03 µg/mL (40.05 µg TE/mg) than diploid with IC50 > 512 µg/mL (12.68 µg TE/mg). Tetraploids exhibited more effective inhibition of in vitro catalytic activity of pro-inflammatory enzyme cyclooxygenase-2 (COX-2) than diploids at 50 µg/mL concentration. Furthermore, molecular docking revealed higher binding affinity of thymol and γ-terpinene towards tested protein receptors, which explained enhanced bioactivity of tetraploid essential oil. In conclusion, these results suggest that synthetic polyploidization using oryzalin could effectively enhance the quality and quantity of secondary metabolites and can develop more efficient essential oil-based commercial products using this induced genotype.
Keywords: fytonutrienty; thymol; Dinitrobenzenes; tetraploidie; Sulfanilamides; oleje prchavé; simulace molekulového dockingu; Thymus Plant; Plant Oils; sulfanilamidy; Thymol; dinitrobenzeny; Oils, Volatile; Tetraploidy; Cyclohexane Monoterpenes; oleje rostlin; monoterpeny s cyklohexanovým kruhem; Phytochemicals; Thymus (rostlina); Molecular Docking Simulation